The Multiplicities Within Capitalist Rule and the Articulation of Struggles - Michael Hardt (tripleC: Communication, Capitalism & Critique, 2018)
This contribution is part of a debate between Michael Hardt/Toni Negri and David Harvey on the occasion of Marx’s bicentenary (May 5, 2018). The discussion focuses on the question of what capitalism looks like today and how it can best be challenged. In this article, Hardt and Negri respond to David Harvey’s article “Universal Alienation”.